2013
DOI: 10.3390/nu5010149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Potential of “Maltese Mushroom” (Cynomorium coccineum) by Means of Multiple Chemical and Biological Assays

Abstract: Cynomorium coccineum is an edible, non-photosynthetic plant widespread along the coasts of the Mediterranean Sea. The medicinal properties of Maltese mushroom—one of the oldest vernacular names used to identify this species—have been kept in high regard since ancient times to the present day. We evaluated the antioxidant potential of fresh specimens of C. coccineum picked in Sardinia, Italy. Both aqueous and methanolic extracts were tested by using multiple assay systems (DPPH, FRAP, TEAC, ORAC-PYR). Total phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 30 publications
2
40
0
2
Order By: Relevance
“…Indeed, the outer, brittle and harder layer of Cynomorium yields the particles with the best quality and highest activity, whilst the peeled, softer inner part may be milled, yet the resulting nanosuspension is less active. Hence, the substances responsible for activity seem to reside primarily-but not exclusively-in the outer layer, a finding in line with previous studies on this plant, which have revealed a high content of biologically active cyanidin 3-O-glucoside in this layer [11]. In contrast, the peeled inner part of the plant, which has in the past on occasion served as food, is less active, probably due to the lack of such substances.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, the outer, brittle and harder layer of Cynomorium yields the particles with the best quality and highest activity, whilst the peeled, softer inner part may be milled, yet the resulting nanosuspension is less active. Hence, the substances responsible for activity seem to reside primarily-but not exclusively-in the outer layer, a finding in line with previous studies on this plant, which have revealed a high content of biologically active cyanidin 3-O-glucoside in this layer [11]. In contrast, the peeled inner part of the plant, which has in the past on occasion served as food, is less active, probably due to the lack of such substances.…”
Section: Discussionsupporting
confidence: 88%
“…The samples were carefully handled as described by us previously [11]. In one part of the samples, the red external layer (EL) and the colourless internal peeled plant (PP) were carefully separated from the whole plant (WP) as exhibited in Figure 2, and the resulting three samples were freeze-dried using Telstar LyoQuest-55 (Milan, Italy) within two hours of the collection.…”
Section: Collection and Preparation Of Plant Materialsmentioning
confidence: 99%
“…In Sardinia, the C. coccineum was used as an astringent in particularly in bleeding and leucorrhoea; the decoction of the aerial part as antidiarrhoeal and the fleshy stem was used to obtain a brown dye using in the weaving (Flora di Sardegna 2014). Recently, Zucca et al (2013) demonstrate that the extracts of C. coccineum show a significant total antioxidant power and also exert an in vitro protective effect in different bioassays of oxidative stress. They evaluated the antioxidant potential of aqueous and methanolic extracts of C. coccineum.…”
Section: Antifungal Activity Of Extracts From Cynomorium Coccineum Grmentioning
confidence: 99%
“…Glucose (Tao et al, 1999), sucrose , ginger oil ketones glucoside (Chaomei et al, 1999 Extract of fresh C. coccineum plant has a hypotensive effect, the active ingredient has not been identified (Ikram et al, 1978). In vitro, C. coccineum extract has an antioxidant potential (Zucca et al, 2013), antiproliferative effects on human cancer lines and antiviral activity against a panel of mammalian viruses (Rosa et al, 2015;Vascellari et al, 2019). In vivo, C. coccineum treatment prolonged a survival of mice with cancer (Sdiri et al, 2018).…”
Section: Saccharides Polysaccharides and Other Sugar Derivativesmentioning
confidence: 99%